HUBUNGAN WORK FAMILY CONFLICT DENGAN BURNOUT SYNDROME PADA PERAWAT DI RUANG RAWAT JALAN RSAB HARAPAN KITA JAKARTA TAHUN 2023 - Aqillah Tasya (2023)
The prevalence of burnout syndrome among nurses at RSAB Harapan Kita Jakarta indicates that nurses face a substantial workload, leading to physical, mental, and emotional exhaustion. The presence of work family conflict can lead to the development of burnout syndrome, ultimately impacting an individual's performance. The objective of this study is to examine the correlation between work family conflict and various factors including age, gender, marital status, education level, and work experience, with the occurrence of burnout syndrome among nurses working in the outpatient department of RSAB Harapan Kita Jakarta. This quantitative cross-sectional research of 65 outpatient nurses used chi-square test analysis. The Maslach-Trisni Burnout Inventory (M-TBI) questionnaire and the Work Family Conflict Scale (WFCS) questionnaire were used for this study. Age (p = 0.050) and work family conflict (p 0.035) were associated with burnout syndrome. However, burnout syndrome was not associated with sex (p = 0.960), marital status (0.072), education level (0.10%), or job period (1.000). In conclusion, work family conlict can affect burnout syndrome in nurses. Nurses who experience work family conflict must be able to balance work with personal life so as not to trigger burnout syndrome.